Risk Management as a Key Element in the Digital Transformation of an Industrial Enterprise - D. S. Pashchenko; N. M. Komarov (Мир новой экономики, 2021)
The Russian industry is entering digital transformation with some delay, and the implementation of accompanying large-scale changes contains a significant number of specific risks. Creating a promising business model and the technological outline of an industrial enterprise that implements it takes place under conditions of high uncertainty. The article proposes a general approach and elements of a practical risk model for planning and carrying out an industrial enterprise’s digital transformation to reduce the uncertainty of the process in its signifiant aspects. The proposed management solutions help reduce the likelihood of a negative impact of accompanying general and specifi risks, build a formalized model of risk management, and increase transparency in managing relevant practical projects. The article also discusses fiancial reserves usage as a tool for active risk management.